Autores - Rivas, Ramón D. (Kóot, 2013)
Rafael Alas Vásquez Tania García Ricardo Ibarra Portillo Lourdes Carbonell Hidalgo Cícero Antonio F. de Almeida José Heriberto Erquicia Cruz Roberto Gallardo Pedro Antonio Escalante Arce